REALIZATION OF FLOUTING MAXIM OF HUMOR IN AMERICAN MOVIE THE UPSIDE - Mutiara . Aisyah; Anni Holila Pulungan; Siti Aisyah Ginting (LINGUISTIK TERAPAN, 2022)
ABSTRACT The aim of this research was to find out the realization of flouting maxim of humor uttered by the characters in the movie The Upside. The research was conducted in descriptive qualitative research design. The script and the subtitle of The Upside movie has become the source of data which represent the flouting maxims of Cooperative Principle by Grice. Then the data were analyzed by read and write technique or attentive observation since the data in the form of utterances. The data also analyzed by choosing the funny utterances only since this research focusing in flouting maxim of humor. The result of this study found the realization of flouting maxim were nine points, that called as overstatement (giving too much information), understatement (giving too little information), metaphor, irony, banter, irrelevant statement, ambiguous statement, tautology and rhetorical question. The most used flouting maxim realized in overstatement, and the lowest rank of flouting maxim were realized in the form of tautology. It was zero data in tautology.